The Kingdon-Khan Model: Acknowledging the Role of Media, Public Opinion, and Social Movements in Agenda-Setting - Khan, Farid Ullah; Smith, Joanna; Meyer, Frauke (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
This article proposes the Kingdon-Khan Model (KKM) as an extension of John Kingdon’s Multiple Streams Model (MSM) of agenda setting. While the MSM is comprehensively used to explain how issues reach policymakers’ agendas, it underrepresents the influence of media, public opinion, and social movements on agenda setting. To address this limitation, the KKM introduces a fourth “social stream” encompassing these interrelated societal forces. Drawing on empirical research on media, public opinion, social movements, and public policy, the authors conceptualize components of social stream and its interactions with the problem, policy, and political streams. The authors illustrate the KKM’s utility through examples of the Black Lives Matter and Pro-Palestinian movements. The KKM enhances the MSM’s explanatory power by accounting for the complex, multidirectional forces influencing contemporary agenda setting.